Dinamika Kelompok Tani Esa Tarendem Di Desa Rurukan 1 Kecamatan Tomohon Timur - Steipi Tiwang; Melsje Yellie Memah; Jane S. Tambas (Sam Ratulangi University, 2022)
This research aims to determine the dynamism in the Esa Tarendem farmer group in Rurukan I Village, East Tomohon District. This research was conducted during June-August 2021. In Rurukan I Village , East Tomohon District, the data used in this study were primary data and sequence data. Primary data were obtained through the method of direct interviews with the Esa Tarendem farmer group using a list of questions / (questionnaires). Meanwhile, secondary data was taken from the Esa Tarendem farmer group in Rurukan I Village, East Tomohon District. The results of this study show that the dynamism of the Esa Tarendem Farmer Group in Rurukan I Village, East Tomohon District, is very dynamic. Where the results of the total alignment score of 263 and the percentage of 97.3 so that they are categorized dynamically. Mathematically, the calculation of Group Dynamics by summing all the total scores from variable measurement indicators. The total score obtained is 263. From the total score obtained, the calculation of the percentage of score acquisition is carried out, namely by sharing the score. The percentage calculation is as follows, the percentage of score gain = 876.4/9=97.3.